A multimodal communication program for aphasia during inpatient rehabilitation: A case study. - Wallace, Sarah E; Purdy, Mary; Skidmore, Elizabeth (NeuroRehabilitation, 2014)
BACKGROUND: Communication is essential for successful rehabilitation, yet few aphasia treatments have been investigated during the acute stroke phase. Alternative modality use including gesturing, writing, or drawing has been shown to increase communicative effectiveness in people with chronic aphasia. Instruction in alternative modality use during acute stroke may increase patient communication and participation, therefore resulting in fewer adverse situations and improved rehabilitation outcomes., OBJECTIVE: The study purpose was to explore a multimodal communication program for aphasia (MCPA) implemented during acute stroke rehabilitation. MCPA aims to improve communication modality production, and to facilitate switching among modalities to resolve communication breakdowns., METHODS: Two adults with severe aphasia completed MCPA beginning at 2 and 3 weeks post onset a single left-hemisphere stroke. Probes completed during each session allowed for evaluation of modality production and modality switching accuracy., RESULTS: Participants completed MCPA (10 and 14 treatment sessions respectively) and their performance on probes suggested increased accuracy in the production of various alternate communication modalities. However, increased switching to an alternate modality was noted for only one participant., CONCLUSIONS: Further investigation of multimodal treatment during inpatient rehabilitation is warranted. In particular, comparisons between multimodal and standard treatments would help determine appropriate interventions for this setting.
Keywords: *Aphasia/px [Psychology]; *Aphasia/rh [Rehabilitation]; *Communication; *Communication Aids for Disabled; *Communication Disorders/px [Psychology]; *Communication Disorders/rh [Rehabilitation]; Aphasia; Article; Communication; Communication Aids for Disabled; Communication Disorders; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Psychomotor Performance; Stroke; Stroke Rehabilitation; Stroke/co [Complications]; Stroke/px [Psychology]; Treatment Outcome; acute rehabilitation; adult; aphasia; case report; cerebrovascular accident; communication aid; complication; dept.cmd; female; hospital patient; human; interpersonal communication; left hemisphere; male; mental performance; middle aged; multimodal treatment; neuropsychological test; psychological rating scale; psychology; psychomotor performance; rehabilitation care; stroke; treatment outcome